2009
DOI: 10.1093/rpd/ncp181
|View full text |Cite
|
Sign up to set email alerts
|

Public exposure to hazards associated with natural radioactivity in open-pit mining in Ghana

Abstract: The results of studies carried out on public exposure contribution from naturally occurring radioactive materials (NORMS) in two open-pit mines in the Western and Ashanti regions of Ghana are reported. The studies were carried out under International Atomic Energy Agency-supported Technical Co-operation Project GHA/9/005. Measurements were made on samples of water, soil, ore, mine tailings and air using gamma spectrometry. Solid-state nuclear track detectors were used for radon concentration measurements. Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 3 publications
4
10
0
Order By: Relevance
“…The reported average annual effective dose for the two mines was 0.3 ± 0.06 mSv (Darko et al 2010). Similar studies carried out on different types of mines in other countries have been reported (UNSCEAR 2000).…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…The reported average annual effective dose for the two mines was 0.3 ± 0.06 mSv (Darko et al 2010). Similar studies carried out on different types of mines in other countries have been reported (UNSCEAR 2000).…”
Section: Introductionsupporting
confidence: 76%
“…The highest absorbed dose rate values of 57.0 and 68.0 nGy h −1 recorded at the soil and water sampling points in Tarkwa Township respectively also compared quite well with the worldwide average value. The results of the study in this mine are also lower than the results of similar studies carried out in other mines in Ghana (Darko et al 2010). Table 4 shows the activity concentrations of 238 U, 232 Th and 40 K in the soil/rock samples as well as the absorbed dose rate and the estimated annual effective doses.…”
Section: Estimation Of Total Annual Effective Dosementioning
confidence: 56%
See 3 more Smart Citations